(untitled) (Perner’s Contacts, 2019)
This paper deals with the study of the possibility of increasing the air quality in urban agglomerations using environmentally friendly types of lorries and specification of their operation. The first chapter of the paper focuses on the creation of low-emission zones in urban centres, specifically on the creation of urban areas. The second chapter of the paper focuses on comparing alternative types of drives today. The third chapter of the paper focuses on the competitiveness of the operation of alternative type vehicles. The aim of the paper is to point out the possibility of reducing the emission burden in the city centre and increasing air quality in cities by placing vehicles with alternative types of drive into service